The Orange Order: a global history - Coleman, Patrick (Studies in British and Irish migration series, 2025)
"The Orange Order, while Irish Protestant-founded, managed in a short period of time to spread to Britain, Canada, the United States, Australia, New Zealand and even Africa. This book examines the order's origins and spread across the world, with a focus on its structure and rituals, activism, parades, material culture and Junior Orange Movement. It integrates the activities of men, women and children and deploys a comparative and transnational framework to identify differences and similarities as the organization developed globally. It argues that despite the best efforts of the Orange Order to challenge its reputation as a male-dominated, bigoted and often violent organisation, this perception endures to this day." --